Molecular identification of Auxis spp. larvae (Pisces: Scombridae) from the Gulf of California: Solving morphological identification limits (Revista de Biología Marina y Oceanografía, 2018)
The larvae of the Auxis genus are abundant in the Gulf of California during summer; however, their identification to the species level by morphological methods is a challenge. The goal of this study was to identify A. thazard and A. rochei larvae for first time, through molecular markers using COI sequences of mtDNA, and look for distinctive morphological characteristics between species, mainly in pigmentation patterns. Larvae were obtained by zooplankton tows in 3 oceanographic cruises in the southern Gulf of California and adjacent waters. The presence of A. thazard and A. rochei larvae was genetically confirmed. The sequences of 7 larvae showed genetic divergences lower than 1% when were compared to sequences of A. thazard adults, while 15 larvae showed genetic divergences lower than 2% when where compared to sequences of A. rochei adults. Genetic divergences between both Auxis species were higher than 2%. These results suggest the spawning of both species in the Gulf of California. On the other hand, pigmentation patterns and morphometric characteristics, in all larval stages, did not permit the secure differentiation between species. Thus, the use of molecular identification by COI is recommended to identify Auxis larvae to the species level, as well as in other marine fish larvae collected in other regions of the world, that have identification troubles.